2022
DOI: 10.7759/cureus.21266
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Immunity Against Hepatitis B Virus After Routine Immunization Among Adults Visiting Primary Care Centers in Riyadh, Saudi Arabia

Abstract: This study aimed to determine the persistence of induced immunity against hepatitis B virus (HBV) among adults routinely vaccinated during their infancy and correlate the level of induced immunity with participant characteristics. MethodologyThis was a cross-sectional study conducted among visitors to primary care centers of the Ministry of Health (MOH) in Riyadh, the Kingdom of Saudi Arabia (KSA) during the period from August 2020 to January 2021. The study population included healthy adults of both genders w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It has been reported that even after HBV vaccination, the prevalence of anti-HBs (such as a marker of immunization that was not reported here) can progressively decrease with age in the presence or absence of anti-HBc. 23 An earlier, population-based survey in Saudi Arabia identified the Southern region and Tabouk province as hyperendemic areas for HBV. 24 It was hypothesized that HBV prevalence in these regions might be influenced by populations of neighboring countries known to be HBV endemic.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that even after HBV vaccination, the prevalence of anti-HBs (such as a marker of immunization that was not reported here) can progressively decrease with age in the presence or absence of anti-HBc. 23 An earlier, population-based survey in Saudi Arabia identified the Southern region and Tabouk province as hyperendemic areas for HBV. 24 It was hypothesized that HBV prevalence in these regions might be influenced by populations of neighboring countries known to be HBV endemic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our finding in terms of blood group frequency among participants agrees with this study. As a result, Saudi Arabia's health authorities, as recommended before by another study [ 17 ], should be encouraged to work together to conduct bigger research comparable to that of [ 15 , 14 ], which followed individuals for thirty years. Our findings support another study that found unsatisfactory levels of protection amongst health care workers who received vaccination during childhood [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an easily accessible factor in an individual's genetic makeup, ABO blood groups have been statistically and biologically associated with many chronic diseases as well as some viral infections [ 13 - 14 ]. The epidemiological studies have explored the relationship between ABO blood group and HBV infection [ 15 ]. However, the results have found that HBV prevalence in a highly endemic area was lower in blood group B, but higher in blood group O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several drugs in advanced stages of clinical development including bulevirtide, JNJ-6379, ABI-H0731, ARO-HBV, and REP-2139, in which expectations indicate that combination therapies of antivirals and immune modulators achieve the maximum benefits of treatment ( Soriano et al, 2020 ). Saudi Arabia is one of the endemic countries with HBV infection in the Middle East ( AlAteeq et al, 2022 ), since 1989, it has implemented a mandatory vaccination program for HBV immunization ( Table 2 ), which has shown significant efficacy in declining cases over the past 20 years ( Ahmad et al, 2022 ).…”
Section: Hepatitismentioning
confidence: 99%